Sustainable Development of Seawater Prawn Farming Associated with Animal Biotechnology - Josfeno Maxreeve, Linggi; Tuan Nur Ain Nazurah, Tuan Mustapha; Kristene Yong, Ling; Nicklaus, George; Shing Yuing, Thian; Hung Hui, Chung (UNIMAS Publisher, 2025)
Aquaculture is the breeding, raising, and harvesting of water living organisms. The aquaculture industry plays a vital role in providing sufficient aquatic food for the world’s growing population in a sustainable way. Besides, this industry also contributed to improving the rights and income of communities, which helps to achieve equitable livelihoods. Moreover, the perfect aquatic food system will also be resilient to human and environmental shocks, including climatic changes (FAO, 2022). In Malaysia, the aquaculture industry has contributed 8.9% to the total national agricultural gross domestic product (GDP) and created 1.75 million (estimated) jobs for Malaysians (Fathi et al. 2018). Within the aquaculture industry, prawn farming has made Malaysia the 9th largest prawn exporter globally. Prawn farming practices in Malaysia were introduced in the 1970s to meet the rising prawn demand-supply, and today it has become one of the major contributors to Malaysia’s GDP.